177Lu-PSMA-I&T Radioligand Therapy for Treating Metastatic Castration-Resistant Prostate Cancer: A Single-Centre Study in East Asians - Bu, Ting; Zhang, Lulu; Yu, Fei; Yao, Xiaochen; Wu, Wenyu; Zhang, Pengjun; Shi, Liang; Zang, Shiming; Meng, Qingle; Ni, Yudan; Shao, Guoqiang; Qiu, Xuefeng; et al. (Frontiers in Oncology, 2022)
Purpose: There is increasing evidence for convincing efficacy and safety of 177Lu-labled prostate-specific membrane antigen (PSMA)-targeted radioligand therapy (PRLT) for metastatic castration-resistant prostate cancer (mCRPC). However, data are not available regarding the feasibility of 177Lu-labled PSMA-targeted RLT in East Asians. The present study summarized the first experience with 177Lu-PSMA-I&T therapy for mCRPC in China. Methods: Forty consecutive patients with mCRPC were enrolled from December 2019 to September 2021. Eligible patients received 177Lu-PSMA-I&T RLT at intervals of 8-12 weeks. Toxicity was assessed based on standardized physicians’ reports and the Common Toxicity Criteria for Adverse Events criteria. Response to PRLT was evaluated according to the changes of prostate specific antigen (PSA) response and imaging response. Quality of life (QOL), Karnofsky performance status (KPS) and pain (visual analogue scale, VAS) were also evaluated. The impacts of baseline parameters on the therapeutic effects were explored by univariate and multivariate logistic regression analyses. Results: All patients underwent a total of 86 cycles of 177Lu-PSMA-I&T (range: 1-5 cycles) with dosages of 3.70-14.43GBq per cycle, with a median of 8 months followed up. Six patients (15%) developed mild reversible xerostomia during follow-up, and 28 patients (70%) experienced grade 1-4 bone marrow dysfunction. Changes in PSA were assessed after therapy, accompanied by the partial response (PR) in 25 patients (62.5%), the stable disease (SD) in 5 patients (12.5%), and the progressive disease (PD) in 10 patients (25%), respectively. QOL, KPS (%) and VAS scores were improved significantly due to treatment (P<0.05). Overweight and elevated AST, ALP, and LDH were associated with poor outcomes. Conclusions: 177Lu-PSMA-I&T achieves the favourable response and well tolerance in mCRPC, which associates with not only PSA decline but also with tumor remission including lymphadenopathy and bone metastasis. We also find that patients with overweight and high AST, ALP, and LDH should be cautious to undergo the PRLT. Large-cohort studies are warranted to confirm the initial findings and elucidate the survival benefit of the treatment.